2019
DOI: 10.1002/ejoc.201900362
|View full text |Cite
|
Sign up to set email alerts
|

Effective Synthesis and Modification of α‐Cyclodextrin‐Based [3]Rotaxanes Enabling Versatile Molecular Design

Abstract: One‐pot synthesis of various α‐cyclodextrin‐(α‐CD‐) based [3]rotaxanes in water and their structural modifications are discussed in detail. Pseudo[3]rotaxane was prepared from α‐CD and α,ω‐diaminododecane in water (above 100 g, quantitative yield in a 1 L flask). Successive urea‐forming end‐capping reactions with isocyanate in water selectively afforded [3]rotaxane with head‐to‐head structured α‐CDs. The yields were varied by bulkiness and functionality of end‐capping agents. Significant modifications of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The said authors used an orthogonal agent containing the acylazide group as the RAFT initiator, and they demonstrated that various vinyl monomers could be polymerized in a living fashion from the initiator. Acylazide species can be easily synthesized starting from carboxylic acids by making the acids react with diphenylphosphoryl azide (DPPA) and then converting the products, thus obtaining reactive isocyanate groups by simple heating. The thus produced acylazide species can be regarded as potential sources of the reactive moiety of the end-reactive polymer. For example, the hydroxyl group of 4-hydroxymethylbenzoylazide ( 1 ) can be utilized to initiate a living ring-opening polymerization of lactone species in mild reaction conditions, which would afford an end-reactive polyester (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The said authors used an orthogonal agent containing the acylazide group as the RAFT initiator, and they demonstrated that various vinyl monomers could be polymerized in a living fashion from the initiator. Acylazide species can be easily synthesized starting from carboxylic acids by making the acids react with diphenylphosphoryl azide (DPPA) and then converting the products, thus obtaining reactive isocyanate groups by simple heating. The thus produced acylazide species can be regarded as potential sources of the reactive moiety of the end-reactive polymer. For example, the hydroxyl group of 4-hydroxymethylbenzoylazide ( 1 ) can be utilized to initiate a living ring-opening polymerization of lactone species in mild reaction conditions, which would afford an end-reactive polyester (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available solvents and reagents were used as received. Pseudo[3]­rotaxane 1 and bulky diisocyanate 2 were synthesized as described in the literature . Poly­(propylene glycol) bis­(2,4-trylene diisocyanate terminated) ( NCO-PPG , M n = 2300) was purchased from Merck Co., Ltd. 1 H NMR spectra were recorded using a Bruker BioSpin AVANCE DPX-300 spectrometer and a Bruker AVANCEIIIHD500 spectrometer utilizing deuterated solvents.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, we developed methods for synthesizing CD-based rotaxanes by end-capping of pseudo[3]­rotaxanes containing 1,12-diaminoalkane axles with bulky phenyl isocyanates. Because [3]­rotaxanes were obtained in good yields, this suggests that pseudo[3]­rotaxane may be a useful comonomer for polyrotaxane synthesis. If we use an end-reactive polymer as a macromonomer for polymerization with pseudo[3]­rotaxane, we can obtain polyrotaxane with a poor CD coverage, which is difficult to synthesize.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the team prepared [48] a head-to-tail orientational isomer with high selectively on an oligophenylene(ethynylene) dumbbell on porous glass solid supports. Selective syntheses of tail-to-tail [49,50] and head-to-head [51][52][53][54] [3]rotaxanes have also been reported (see Section 3.1.2). A [3]rotaxane based on oligothiophene-threaded β-CD rings has also been synthesized [55] as a mixture of orientational isomers.…”
Section: Methodsmentioning
confidence: 99%